Pembuatan Transfer Foto Ke Kayu Dengan Perekat Df74 Sebagai Salah Satu Usaha Di Tempat Wisata - Kusno Yuli Widiati; Irvin Dayadi; Karyati; Karmini (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2022)
Wood photo transfer is one method of printing photos uniquely, it is more waterproof and lasts longer with proper treatment. The wood materials used can come from wood waste, plywood, kitchen utensils, and home furnishings. Because it is unique and the manufacture is quite fast and easy using DF74 adhesive, the purpose of the photo transfer community service is to create an opportunity to open a business. Community service is carried out in the village of Bukit Biru, Tenggarong sub-district has a waterfall tourist location and Bukit Biru Peak. The method of devotion carried out is applicable by directly practicing how to wood photos transfer. The results of the photo transfer community service made the public understand and be able to practice photo transfer easily. Tenggarong City is a place where wood sources are still easily available and DF 74 adhesive can also be purchased online, making photo transfer business prospects quite promising.